Recommendations of the Polish Association of Neuropathologists on performing post-mortem examination of the brain and spinal cord - Sejda, Aleksandra; Wierzba-Bobrowicz, Teresa; Michalak, Sławomir; Adamek, Dariusz; Gulczyński, Jacek; Ciołkowski, Maciej; Grajkowska, Wiesława; Iżycka-Świeszewska, Ewa (Polish Journal of Pathology, 2023)
Neuropathological central nervous system (CNS) post-mortem examination is a highly specialistic element of the autopsy procedure with methodological specificity. Herein we propose updated recommendations for CNS autopsy for pathologists and neuropathologists. The protocol includes the compendium of neuroanatomy with current nomenclature, consecutive steps of gross examination, as well as appropriate sampling algorithms in different clinical and pathological settings. The significance of pathoclinical cooperation in differential diagnosis is exposed. We believe it is essential to create and promote the guidelines to improve the quality of CNS post-mortem examination at the national level.